Self-Adaptive Solar Panel - Sangeetha, M.; Jayalakshmi, C.; Janani Shree, K.K.; Kabila, M.; Kamalika, G.; Vasishta, C.V. (Journal of Neonatal Surgery, 2025)
This project focuses on designing a self-adaptive solar panel system that optimizes energy efficiency by using Internet of Things (IoT) technology. The system integrates sensors, servo motors, and a microcontroller, allowing the panel to adjust its orientation dynamically in response to varying sunlight intensity and environmental conditions. Through real-time monitoring and control, enabled by an IoT platform, users can track and manage energy performance remotely. By overcoming the limitations of traditional fixed-position solar panels, this scalable solution enhances renewable energy utilization and contributes to environmental sustainability.